1988
DOI: 10.1002/ajpa.1330750408
|View full text |Cite
|
Sign up to set email alerts
|

General body growth in children with cleft palate and related disorders: Age differences

Abstract: Clefts of the lip and palate, separately or in combination, are among the most frequent congenital defects seen today. Their etiology is heterogeneous and may include hormonal factors, which suggest the possibility of growth effects. Whether affected children are smaller than others has not been determined. We recently showed that growth status is associated with type of cleft. We hypothesized genetic alterations in metabolic pathways that alter prenatal growth, producing clefts; some of these alterations also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Differences between cross-sectional studies of growth accomplishment and the longitudinal approach in individual children used here also may contribute to discrepancies among studies, as Tanner (1962) has emphasized. The results presented here confirm the earlier anthropometric results from my colleagues and my earlier work, which showed that growth accomplishment in children with clefts differs by both cleft type and chronological age (Bowers et al, 1987(Bowers et al, , 1988a. This work also replicates Prahl-Andersen's findings of advanced SA in girls with CLP (Prahl-Andersen, 1979).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Differences between cross-sectional studies of growth accomplishment and the longitudinal approach in individual children used here also may contribute to discrepancies among studies, as Tanner (1962) has emphasized. The results presented here confirm the earlier anthropometric results from my colleagues and my earlier work, which showed that growth accomplishment in children with clefts differs by both cleft type and chronological age (Bowers et al, 1987(Bowers et al, , 1988a. This work also replicates Prahl-Andersen's findings of advanced SA in girls with CLP (Prahl-Andersen, 1979).…”
Section: Discussionsupporting
confidence: 94%
“…Krogman had argued that children with clefts usually reached heights within the normal range (1979). Our earlier work, however, appeared to indicate that they have growth defects (Bowers et al, 1987(Bowers et al, , 1988a. We had found that children with bony clefts have altered bone growth throughout their bodies, as seen in their reduced elbow breadths (Bowers et al, 1988b).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations